PENGAMBILAN KEPUTUSAN PETANI DALAM PEMILIHAN KOMODITAS HORTIKULTURA DI LAHAN PASIR PANTAI KECAMATAN SANDEN KABUPATEN BANTUL - , NUR HILDAN D; , Ir. Roso Witjaksono, MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine the farmers decision making for the selection of horticultural commodities and the factors that influence it, to know the effect of farmers decision making for the selection of horticultural commodities and other factors on the horticultural cultivation adoption technology. The method used in this research was descriptive method with survey techniques. Sampling was carried out of the village and farmer groups purposively, whereas farmers sample with simple random sampling. The total sample is 60 farmers, 30 farmers from Manunggal Farmers Group and 30 farmers from Pasir Makmur Group, in Srigading Village. Data were analyzed by Chi-Square test. The results showed that farmers decision making in the selection of horticultural commodities was performed by Mother 10%, 31% was performed by Mother and Father (no dominant) 18.33%, Mother and Father (predominantly mothers) 5% than Mother and Father (predominantly fathers) 34.67%. The basic of consideration in farmer decision making for the horticulture commodities selection are: suitability of the climate/weather, group agreements, availability of production matterial, capital availability, and price outlook. Level of education, attitudes, land size, and farmer activities in extension affects the decision making of farmers in the selection of horticultural commodities. Capital, farmer age, and farmer motivation does not affect the decision making of farmers in the selection of horticultural commodities.